Tradition - Shils, Edward (London, Faber and Faber, 1981)
This pioneering study by the eminent sociolo- gist Edward Shils presents a comprehensive, analytical treatinent of the notion of 'tradition'. It deals with tradition in general and with its specific forms and modes of operation in such fields as social institutions, art, literature, sci- ence and scholarship. While rejecting an assumed conflict or tension between tradition and change (Shils argues that there is no tradi- tion without change and no change without tradition), it provides a vigorous defence of tradition against those who regard it simply as a clog to progress. The result is an outstanding piece of intellectual history which contains some trenchant criticism of received ideas. Edward Shils is Distinguished Service Professor in the Department of Sociology at the University of Chicago and is also a Fellow of Peterhouse, Cambridge. Tradition is based on the 1974 T.S. Eliot Memorial Lectures which he delivered at the University of Kent.
Keywords: Social sciences